2022
DOI: 10.1109/access.2021.3139183
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Software Effort Estimation Based on Optimizing Correction Factors and Multiple Linear Regression

Abstract: Date of publication xxxx 00, 0000, date of current version xxxx 00, 0000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…The investigator claimed that these parts are insignificant concerning the effort estimation. Recently, Nhung et al [41] optimized the correction factors (ECF and TCF) and multiple regression models to improve the estimation accuracy of the modified UCP.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigator claimed that these parts are insignificant concerning the effort estimation. Recently, Nhung et al [41] optimized the correction factors (ECF and TCF) and multiple regression models to improve the estimation accuracy of the modified UCP.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, these approaches showed promoting results by expanding the complexity weight in the original UCP method. Despite Nhung et al [41] and Hoc et al [54] conducted the optimization in UCP. However, they do not explore the potential of continuous complexity weight level in terms of optimization function.…”
Section: Related Workmentioning
confidence: 99%
“…According to [7], [70], and [71], the Mean Magnitude of Relative Error (MMRE) and Mean Magnitude of Relative Error Relative (MMER) criteria are the most common metrics used. However, [72], [73], and [74] have demonstrated that these methods are biased. Azzeh et al [75] recommend using unbiased methods instead.…”
Section: Evaluation Criteriamentioning
confidence: 99%
“…Another optimization technique was discussed in the work of Nhung et al [42], where a parametric approach toward effort estimation is applied. This work predominantly focuses on numerous regression models to control the errors in estimation using least squared regression towards all the elements in points of use cases.…”
Section: Related Workmentioning
confidence: 99%